Pengaruh Strategi Pemasaran dan Kepuasan Pelanggan Terhadap Keputusan Pembelian Kopi Tomoro Di Outlet Grand Batavia Kab. Tangerang Tahun 2024-2025 - Lukman Nul’hakim; Aida Sapitri (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. This study aimed to determine the effect of marketing strategy and customer satisfaction on purchasing decisions at Kopi Tomoro at the Grand Batavia Outlet in Tangerang Regency. The research method used was a quantitative method with an associative approach. Data collection techniques were carried out by distributing questionnaires to 100 respondents. Data analysis used multiple linear regression tests, t-tests (partial), f-tests (simultaneous), and coefficients of determination. The results of the study indicated that partially marketing strategies did not have a significant effect on purchasing decisions, with a t-count value of 0.381 smaller than the t-table of 1.98472 and a significance value of 0.704 > 0.05. Meanwhile, customer satisfaction had a positive and significant effect on purchasing decisions with a t-count value of 13.435 greater than the t-table of 1.98472 and a significance value of 0.000 < 0.05. Simultaneously, marketing strategy and customer satisfaction significantly influenced purchasing decisions, with a calculated f-value of 588.298, greater than the f-table of 3.090, and a significance value of 0.000 < 0.05. The coefficient of determination indicates that both independent variables were able to explain purchasing decisions by 92.2%. This research was expected to be a consideration for companies in improving marketing strategies and service quality to improve customer purchasing decisions. Keywords: Marketinf Strategy, Customer Satisfaction, Purchasing Decisions.